2019
DOI: 10.1016/j.jor.2019.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Early perioperative complication rates and subsidence with the Tribute® short cementless, tapered stem in primary total hip arthroplasty

Abstract: This study examined early perioperative complications and subsidence following total hip arthroplasty (THA) with a short femoral stem. A retrospective review of 207 consecutive patients (247 hips) having undergone THA via the direct anterior approach produced only six perioperative complications: two intraoperative fractures, three perioperative femur fractures and one dislocation. Subsidence greater than 5 mm was observed in four hips but subsidence did not progress greater than 3 mm at the latest follow-up. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Finally, short uncemented stems are associated with significantly reduced primary stability (Ong et al, 2009), and although our results are encouraging, they cannot provide a definite answer as to the primary stability of shortened stems. A recent study evaluating early outcomes of THA using a comparable shortened stem to the one evaluated in this study, but collarless, found encouragingly low rates of stem subsidence, which exhibited no progression after 6 months (Attenello et al, 2019). It is nevertheless important to note that CFR alone cannot predict stem subsidence, good osseointegration or load transmission, so that further investigation remains necessary to evaluate the success of shortened stems.…”
Section: Discussionmentioning
confidence: 61%
“…Finally, short uncemented stems are associated with significantly reduced primary stability (Ong et al, 2009), and although our results are encouraging, they cannot provide a definite answer as to the primary stability of shortened stems. A recent study evaluating early outcomes of THA using a comparable shortened stem to the one evaluated in this study, but collarless, found encouragingly low rates of stem subsidence, which exhibited no progression after 6 months (Attenello et al, 2019). It is nevertheless important to note that CFR alone cannot predict stem subsidence, good osseointegration or load transmission, so that further investigation remains necessary to evaluate the success of shortened stems.…”
Section: Discussionmentioning
confidence: 61%
“…Our findings are comparable with the 2018 Australian implant registry data showing a 3.5% revision rate at five years for the AMIStem-H® combined with the same cup [ 9 ], but are higher than those reported for other short stems implanted through the DAA. In a retrospective review of 247 consecutive THAs with the Tribute® short stem, Attenello et al [ 10 ] reported a femoral stem subsidence of more than 5 mm in four hips, and none required revision surgery at 27-month follow-up. In a retrospective review of 899 consecutive patients followed up to 24 months, Cidambi et al [ 11 ] found a 1.3% revision rate for femoral aseptic loosening of a short, mediolaterally tapered stem.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, some orthopedic surgeons used shorter femoral stems to reduce the risk of periprosthetic fractures and muscle injuries [8]. Short stems have been frequently used in THA [9], as they have a small surgical incision, thereby preserving more bone tissues and providing more favorable surgical conditions [10,11]. Previous trials revealed a short-term survival of 94-100% and an incidence of thigh pain of 4%-18% in patients receiving THA with short stems [8,9,[12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%